Konasi Komunitas Pesantren Yogyakarta dalam Penggunaan Arabic Terms dan Indonesian Terms pada Skim Produk Bank Syariah - Abdul Ghoni; Teguh Suripto; Abdullah Salam (AL-FALAH : Journal of Islamic Economics, 2016)
This study analyzes the pesantren community “konasi” comparison to the use of terms and Indonesian Arabic terms used in the skim product of Islamic banks. The sample is pesantren communities in the Province of D.I Yogyakarta. Types of samples in this study using cluster random sampling and proportionate sampling. Samples were taken as many as 155 respondents from 31 boarding schools in the Province D.I Yogyakarta. The results showed no difference konasi pesantren communities involving caregivers, religious teacher and students in the province DI Yogyakarta against the use of terms and Indonesian arabic terms. Keywords: arabic terms, Indonesian terms, konasi, product